Riba: Transaksi Kotor Dalam Ekonomi - Fatkhul Wahab (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2017)
In conducting various economic activities, Muslim society is often faced with the problem of usury. Seen to be a problem because usury is a normative thing that is forbidden religion and applicative apparently detrimental to certain parties. In Islam, levying usury or obtaining profit in the form of borrowing usury is haram. Prohibition of usury in various transactions of economic activity, presents the consequence that all economic activities should be clean and free from the element of usury. The writing of this article aims to reveal the nature of usury, the type of usury, the cause of prohibition of usury and the negative side or adverse effects of usury in economic activities. The author concludes, among other things: the negative impact of usury is causing discord and dissatisfaction among society and resulted in economic instability. Keywords: Riba, Islamic Law, Islamic Economics